A case of Appalachian endemism: Revision of the Cambarus robustus complex (Decapoda: Cambaridae) in the Kentucky and Licking River basins of Kentucky, USA, with the description of three new species - Loughman, Zachary J.; Henkanaththegedara, Sujan M.; Fetzner Jr., James W.; Thoma, Roger F. (Zootaxa, 2017)
The amazing levels of freshwater biodiversity found in the Appalachian Mountains of the eastern United States are among the highest recorded globally. Localized endemics make up much of this diversity, with numerous fish, freshwater mussels, salamanders and crayfish often being restricted to a single watershed, and in some instances, subwatersheds. Much of this diversity is the product of the processes of vicariance and historical stream drainage patterns. Herein, we describe three new crayfish species, all previously members of the Cambarus robustus complex, which occur in the Appalachian portion of the Kentucky and Licking river basins in Kentucky, USA. All three species differ from each other morphologically, genetically, and zoogeographically, fulfilling the requirements of the integrated species concept. Cambarus guenteri occurs in the southern tributaries of the Kentucky River mainstem as well as throughout the South Fork Kentucky River. Cambarus taylori is a narrow endemic, which only occurs in the Middle Fork Kentucky River. Cambarus hazardi, which has the widest distribution of the three new species, occurs in the North Fork Kentucky River, Red River, and upper reaches of the Licking River basin. Stream piracy events between the Cumberland and South Fork Kentucky River, as well as the Licking, Red and North Fork Kentucky rivers, are theorized to be important in the evolution of this complex. Cambarus guenteri is proposed as currently stable, though both C. taylori and C. hazardi are considered imperiled at this time due to habitat destruction throughout both of their respective ranges.